Redundant multi-mode filter for a navigation system - Allerton, David J.; Jia, Huamin (Institute of Electrical and Electronics Engineers (IEEE), 2007)
An approach is introduced to the design of a multi-mode navigation filter to combine a low-cost skewed redundant inertial measurement unit (SRIMU) with a multifunctional GPS (MF-GPS) receiver in order to implement a fault-tolerant aircraft navigation system, which can achieve the required navigation performance of conventional systems in terms of accuracy, integrity, continuity, and availability. The MF-GPS receiver provides raw GPS measurements for pseudo- range and range rate to compute the navigation solutions (position and velocity) and also multi-antenna carrier phase interferometric measurements to estimate the aircraft attitude solution, if the carrier phase data is reliable. A multi- mode navigation filter is designed which combines state and measurement fusion methods and processes the SRIMU and raw MF-GPS outputs to provide reliable position, velocity and attitude information, and also kinematic parameters required in control, guidance, and navigation applications. The feasibility and performance of this integrated design is assessed and evaluated by using simulation. The accuracy of inertial gyros used in the evaluation ranges from 1 ± /h to 30 ± /h, including low-cost inertial sensor technologies. The simulation studies presented here show that a multi-mode navigation filter can achieve sufficient reliability and accuracy and that SRIMU/MF-GPS integrated navigation systems may provide a cost-effective system for future regional aircraft, general aviation aircraft, and unmanned aerial vehicle